2005
DOI: 10.1007/s00330-005-2741-x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of liver metastases under 2 cm: comparison of different acquisition protocols in four row multidetector-CT (MDCT)

Abstract: This study compared different acquisition protocols performance to detect small liver metastases (<2 cm). Thirty consecutive patients with histologically proven hepatic metastases were explored by MDCT at the liver equilibrium phase by four successive acquisitions. We compared the following protocols (1-4): 5/30/1.5 (section thickness/table speed/pitch); 5/15/0.75; 5/11.25/0.75; and 2.5/15/1.5 with the same X-ray dose. The gold standard was based on patient radiological follow-up. Evolutive lesions were consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 28 publications
(36 reference statements)
0
22
0
Order By: Relevance
“…For the MDCT imaging, three-phasic dynamic images, including arterial, portal venous, and equilibrium phases, were acquired at 3 mm reconstruction thickness, using a detector collimation of 1.5 mm. Recent study about determining the optimal CT protocol for detection of hepatic metastases using four-slice MDCT [30] has shown that a thin section of 2.5 mm or an increased table speed are less efficient in detecting small metastases, even though MDCT with a different detector configuration from ours was used in that study. Moreover, we utilized a highly concentrated iodine contrast agent [31,32] to maximize the lesion-to-liver contrast.…”
Section: Discussionmentioning
confidence: 84%
“…For the MDCT imaging, three-phasic dynamic images, including arterial, portal venous, and equilibrium phases, were acquired at 3 mm reconstruction thickness, using a detector collimation of 1.5 mm. Recent study about determining the optimal CT protocol for detection of hepatic metastases using four-slice MDCT [30] has shown that a thin section of 2.5 mm or an increased table speed are less efficient in detecting small metastases, even though MDCT with a different detector configuration from ours was used in that study. Moreover, we utilized a highly concentrated iodine contrast agent [31,32] to maximize the lesion-to-liver contrast.…”
Section: Discussionmentioning
confidence: 84%
“…The limited attenuation difference that can often occur between hepatic lesions and the surrounding normal liver tissue [12] may compromise dose optimisation since high exposures aimed at reducing image noise and maximising low-contrast resolution may be required [13].…”
Section: Advances In Knowledgementioning
confidence: 99%
“…Nevertheless, tradeoffs between axial resolution and noise can be envisaged to optimize CT protocols for an envisaged clinical application 7. Previous studies have tested various protocols to find the slice thickness,8, 9, 10 slice spacing,11, 12 or interpolation algorithm13 that would give the best compromise between z ‐axial resolution and noise. Although the physical relationships between axial resolution and noise in CT are long known, the stochastic influence of z ‐axial PVE on the contrast of small objects has never been taken into account.…”
Section: Introductionmentioning
confidence: 99%